(untitled) (Experimental biology, 2022)
It should be noted that at present, much more attention is being paid to the study of higher and semi-aquatic plants due to their wide practical significance. Higher aquatic plants perform the following functions in ponds: filtrative, absorptive, storaging, oxidizing, detoxifying. Also, this kind of plant is used as a raw material for paper, medicine and perfume industries, building materials and fertilizers. As a result of the research, 46 species of higher and semi-aquatic plants belonging to 21 families and 43 genera were identified within Zhalanashkol lake flora. Thus, the species identification process of semi-aquatic vegetation makes it possible to characterize the ecological state of the ecosystem in detail. Nowadays, water analysis is commonly performed with the help of biological indicators, and is widely used in the practice of hydrobiological research.